Modelling inbound international tourism demand in small Pacific Island countries. Issue 10 (25th February 2020) - Kumar, Nikeel; Kumar, Ronald Ravinesh; Patel, Arvind; Hussain Shahzad, Syed Jawad; Stauvermann, Peter Josef
ABSTRACT: In this study, we estimate inbound international tourism demand models at the individual source market-destination and overall destination levels for Fiji, Cook Islands, Tonga and Vanuatu from 2002Q1 to 2016Q2 and Samoa from 2002Q4 to 2015Q3. Tourism demand is measured by visitor arrivals, tourism prices, the source country's real GDP, tourism prices in substitute destinations, seasonality and structural breaks, all of which are considered plausible determinants. The models are estimated using the ARDL-bounds approach, structural breaks are identified using the Bai and Perron break test, and seasonality is tested using the US Census Bureau's X-13 ARIMA-SEATS methodology. The study is important because it presents new evidence on price, income, and substitute price sensitivity, word of mouth, seasonality, and structural-breaks effects in Pacific island destinations.